EFEKTIFITAS PROGRAM CORPORATE SOCIAL RESPONSIBILITY PADA BAITUL MAL MUAMALAT LHOKSEUMAWE BAGI MASYARAKAT - Yoesoef, Yoesrizal Muhammad; Marlida, Marlida (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2019)
This study aims to analyze the effectiveness of corporate social responsibility (CSR) programs for the community. The results showed that: 1) The implementation of the BMM CSR Program of Lhokseumawe City was further developed by Baitul Maal Muamalat Lhokseumawe in order to be distributed appropriately and effectively, the programs are: a) Economic empowerment especially micro-economics b) Educational empowerment program. c) Social and humanitarian empowerment 2) Obstacles in carrying out the Corporate Social Responsibility (CSR) Program in BMM Lhokseumawe City, are: a) Beneficiaries of compensation are higher than existing funds, b) There are people who do not understand yet about the community economic empowerment contract in the form of community economic empowerment qardhu hasan, so that many borrowers do not return it, consequently impacting on the next mustahik, c) The level of recipients of compensation is getting higher and higher, while the funds collected for each month do not add up to what is expected. With the results of the research that have been obtained, it is expected that going forward To the BMM Management Lhokseumawe City in order to increase instruction of activities to subordinate managers or commonly referred to employees, both directing operational products contained in BMM, and other directives. Keywords: Analysis of Corporate Social Responsibility (CSR), BMM (Baitul Mal Muamalat) Abstrak Penelitian ini bertujuan menganalisa bagaimana efektifitas program-program corporate social responsibility (CSR) bagi masyarakat.Hasil penelitian menunjukkan bahwa : 1) Pelaksanaan Program CSR (Corporate Social Responsibility) BMM Kota Lhokseumawe itu dikembangkan lagi oleh pihak Baitul Maal Muamalat Lhokseumawe agar dapat disalurkan secara tepat dan efektif, yaitu: a) Pemberdayaan ekonomi khususnya ekonomi mikro b) Program pendayagunaan pendidikan. c) Pendayagunaan sosial dan kemausiaan 2) Kendala dalam menjalankan Program Corporate Social Responsibility (CSR)Pada BMM Kota Lhokseumawe yaitu: a) Penerima santunan lebih tinggi daripada dana yang ada, b) Masih terdapat masyarakat yang tidak memahami akan akad pemberdayaan ekonomi masyarakat dalam bentuk qardhu hasan, sehingga banyaknya peminjam yang tidak mengembalikannya, akibatnya imbas kepada mustahik yang selanjutnya, c) Tingkat penerima santunan semakin hari semakin tinggi, sedangkan dana yang terkumpul untuk setiap bulannya tidak terdapat penambahan sesuai dengan yang yang di harapkan. Dengan hasil penelitian yang sudah di dapatkan maka diharapkan untuk kedepannya Kepada Manajemen BMM Kota Lhokseumawe agar dapat meningkatkan pengarahan-pengarahan kegiatan kepada manajer bawahan atau biasa disebut dengan karyawan, baik itu pengarahan operasinal produk-produk yang terdapat pada BMM, maupun pengarahan lainnya. Kata Kunci:Corporate Social Responsibility (CSR), BMM (Baitul Mal Muamalat) Lhokseumawe